Risk Assessment of Photokeratitis Among the Welders of Gamelan Gongs in Ponorogo, Indonesia - Rizqy Kartika Sari; Y. Denny A. Wahyudiono; Bachtiar Chahyadhi; Khairul Anwar (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Welding is one of the activities in the manufacture of gamelan gong which has the potential for causing photokeratitis in workers. Photokeratitis can occur as a result of acute exposure to UV rays in the eyes of workers. Risk assessment was used to determine the magnitude of the risk of several factors causing photokeratitis. The purpose of the study was to analyze the risk of photokeratitis among the welders of gamelan gongs in Ponorogo Regency based on the concept of epidemiology. Methods: The research design was cross sectional which was carried out during the Covid-19 pandemic in May 2021. The population of this study was welders making gamelan gongs in Ponorogo, Indonesia. There were six respondents selected using the non-probability sampling technique. Data was collected by interviews, discussions, and observations. The variables, namely host, agent, and environment, were identified as risk factors, then risk analysis was carried out using the semi-quantitative technique by taking into account the level of frequency and severity. The risk evaluation was completed using the ALARP concept. Results: The causative factors of photokeratitis found within the host category were age and working period, which was considered moderate risk, and PPE use behavior, which was considered high risk. In the agent category, the intensity of UV exposure was considered high-risk. The environmental factors, namely working time, exposure distance, and welding location were considered moderate risk. Conclusion: The factors of photokeratitis still exist, thus continuous control efforts are needed.